2016
DOI: 10.3835/plantgenome2015.10.0103
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics Related to Adaptation in Elite Oat Germplasm

Abstract: Six hundred thirty five oat (Avena sativa L.) lines and 4561 single-nucleotide polymorphism (SNP) loci were used to evaluate population structure, linkage disequilibrium (LD), and genotypephenotype association with heading date. The first five principal components (PCs) accounted for 25.3% of genetic variation. Neither the eigenvalues of the first 25 PCs nor the cross-validation errors from K = 1 to 20 model-based analyses suggested a structured population. However, the PC and K = 2 model-based analyses suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
87
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(101 citation statements)
references
References 59 publications
12
87
2
Order By: Relevance
“…FST‐based analysis by Esvelt Klos et al . () failed to identify these major translocation regions, and this may further demonstrate the improved sensitivity of the pcadapt method. These two chromosome representations were assigned by Oliver et al .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…FST‐based analysis by Esvelt Klos et al . () failed to identify these major translocation regions, and this may further demonstrate the improved sensitivity of the pcadapt method. These two chromosome representations were assigned by Oliver et al .…”
Section: Discussionmentioning
confidence: 79%
“…As haplotype structure is related to LD, these differences are consistent with differences in LD decay observed by Esvelt Klos et al . () and may indicate footprints of adaptive QTL. These differences could have resulted from natural or artificial selection during breeding for different agro‐climatic conditions (e.g., northern vs. southern or spring vs. winter production).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong DTF QTL on Mrg02/9D coincides with FHB in TASSEL. Furthermore, the Mrg12/13A DTF QTL, the strongest in Norwegian conditions (Esvelt Klos et al., ), coincides with FHB in TASSEL and FHB and DON in PLSR. We hypothesize that due to photoperiod sensitivity, lines from the Midwest may have a precocious flowering in very long days and possibly immature cell walls, making them very susceptible.…”
Section: Discussionmentioning
confidence: 96%
“…In recent studies, this SNP marker platform has been expanded to utilize a 6k Illumina chip (Tinker et al., ), and these markers have been supplemented using a genotyping‐by‐sequencing (GBS) platform (Huang, Poland, Wight, Jackson, & Tinker, ). Combining these resources, two foundation studies were developed: a consensus map based on the larger set of markers mapped in 12 populations (Chaffin et al., ), and a study of diversity and population structure, including a GWAS analysis of heading date in 635 oat lines (Esvelt Klos et al., ). As this prior analysis confirmed that the primary population structure present in oat is related to spring vs. winter habit, the current work is focused on a set of spring oat varieties that are a subset of the 635 oat lines used in the aforementioned work.…”
Section: Introductionmentioning
confidence: 99%